Preliminary study on extraction and synthesis of biodiesel from jatropha curcas seeds and soybean - Yunus, Robiah; Chang, P. Y.; Lee, L. H.; Azhari, Azhari (2006)
Solvent extraction with hexane has been evaluated for extraction of oil from Jatropha curcas L. seeds and soybean. Experimentally, the effects of time, temperature and size on the extraction yield were investigated. It was found that oil extraction with hexane has high efficiency, while the extraction yield was affected by extraction time, temperature and size. Reduction in particle size, coarse to powder grinded, had effectively increased the extraction yield by more than 6.4%, whereas an increase in temperature from room temperature to 70oC moderately accelerated the extraction process for both jatropha and soybean. Continuous heating of the oil above boiling point (68oC – 70o) of solvent should be avoided as evaporation and degradation of oils components reduced the extraction yield. The optimum extraction yields obtained for both jatropha and soybean were 43% and 23% at 135 and 75 minutes respectively. Transesterification of jatropha and soybean oils to produce jatropha oil methyl ester (JOME) and soybean oil methyl esters (SOME) were carried out. The process was carried out at reaction conditions; temperature 60oC and 70oC and at methanol to oil molar ratio 6:1. Potassium hydroxide (KOH) was used as a catalyst and reaction time of 60 minutes. Increasing temperature from 60oC to 70oC resulted in lower conversion to both JOME and SOME. Soybean oil shows better conversion compared to conversion of jatropha oil to methyl ester with most of the triglycerides of soybean oil was converted to methyl ester.